Feminationalisme en hoe vrouwen belangrijk worden in het maatschappelijk debat over migratie en integratie. - Schrover, Marlou (TSEG - The Low Countries Journal of Social and Economic History, 2020)
Women’s organizations fighting for rights for immigrant women emphasized the suppression of women within Islam. There was little attention to the labour market position of immigrant women, and a lot of attention to violence and lack of rights. Debates feminized and Islamitized at the same time. Arguments used by organizations fighting for immigrant women’s rights were appropriated by right-wing populist parties. This is called femi-nationalism. Right-wing parties also appropriated the gay rights discourse (homo-nationalism). The right-wing populist parties did so extensively, but as this article shows, so did other parties.